Fabricating porous, photo‐crosslinked poly(trimethylene carbonate) membranes using temperature‐induced phase separation†. (29th September 2016) - Pasman, Thijs; Grijpma, Dirk W.; Stamatialis, Dimitrios F.; Poot, André A.
Abstract : The recent development of lungs‐on‐chips is a major advancement in lung disease research. However, the materials used for the membranes in these chips, e.g. poly(dimethyl siloxane) and silicon, are not ideal. This study uses the more biocompatible and mechanically favorable polymer poly(trimethylene carbonate) (PTMC). Porous membranes were made of high molecular weight linear PTMC (250, 000 g/mol) via temperature‐induced phase separation with ethylene carbonate, followed by ultraviolet (UV)‐light crosslinking with pentaerythritol triacrylate and Irgacure 2959. Membrane morphology and crosslinking efficacy was investigated. Membranes with micrometer‐sized pores could be made. There was variation between the different membrane sides in terms of pore size and distribution. Cooling during UV‐light crosslinking resulted in more homogeneous membrane pores, both in size and distribution, and raised the gel content from 48% to 73%, which can be further enhanced by adjustment of the UV treatment or the amount of crosslinking agents. All membranes were highly permeable to water suggesting that nutrient transport, when used with cells, is not limited by the membranes. Here, we show the development of thin and porous PTMC membranes for lungs‐on‐chips, Transwell® inserts and other cell culturing applications. Copyright © 2016 John Wiley & Sons, Ltd.